Double-chamber plethysmography versus oscillometry to detect baseline airflow obstruction in a model of asthma in two mouse strains. (14th September 2021) - Boucher, Magali; Henry, Cyndi; Khadangi, Fatemeh; Dufour-Mailhot, Alexis; Bossé, Ynuk
Abstract: Aim of the study: The current gold standard to assess respiratory mechanics in mice is oscillometry, a technique from which several readouts of the respiratory system can be deduced, such as resistance and elastance. However, these readouts are often not altered in mouse models of asthma. This is in stark contrast with humans, where asthma is generally associated with alterations when assessed by either oscillometry or other techniques. In the present study, we have used double-chamber plethysmography (DCP) to evaluate the breathing pattern and the degree of airflow obstruction in a mouse model of asthma. Materials and Methods: Female C57BL/6 and BALB/c mice were studied at day 1 using DCP, as well as at day 11 using both DCP and oscillometry following a once-daily exposure to either house-dust mite (HDM) or saline for 10 consecutive days. Results: All DCP readouts used to describe either the breathing pattern (e.g., tidal volume and breathing frequency) or the degree of airflow obstruction (e.g., specific airway resistance) were different between mouse strains at day 1. Most of these strain differences persisted at day 11. Most oscillometric readouts (e.g., respiratory system resistance and elastance) were also different between strains. Changes caused by HDM were obvious with DCP, including decreases in tidal volume, minute ventilation, inspiratory time and mid-tidal expiratory flow and an increase in specific airway resistance. HDM also caused some strain specific alterations in breathing pattern, including increases in expiratory time and end inspiratory pause, which were only observed in C57BL/6 mice. Oscillometry also detected a small but significant increase in tissue elastance in HDM versus saline-exposed mice. Conclusions: DCP successfully identified differences between C57BL/6 and BALB/c mice, as well as alterations in mice from both strains exposed to HDM. We conclude that, depending on the study purpose, DCP may sometimes outweigh oscillometry.